Students’ Critical Thinking Skills in Learning Science at Subject Structure and Function of Plant Networks using The Project-Based Learning Model in Class VIII MTs Muhammadiyah 02 Pekanbaru - Safitri, Rani; Sholihat, Neng; Purwanto, Hadi (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2022)
This study aimed to see how students' critical thinking skills were applied after the Project-Based Learning model was applied. This research is experimental research with Two-Group Pretest-Posttest Design. The population of this research was of 216 students. The sampling technique used was a simple random sampling technique, 36 students for the experimental class and 36 for the control class. The instrument used is a test. The hypothesis testing using a t-test found that the tcount was higher than ttable (2,399>1,688). From the results of the analysis, it was found that there were significant differences in students' critical thinking skills with the Project-Based Learning model compared to the conventional model.ABSTRAK: Penelitian ini bertujuan untuk melihat bagaimana kemampuan berpikir kritis siswa diterapkan setelah model Pembelajaran Berbasis Proyek diterapkan. Penelitian ini merupakan penelitian eksperimen dengan Two-Group Pretest-Posttest Design. Populasi penelitian ini sebanyak 216 siswa. Teknik pengambilan sampel yang digunakan adalah teknik simple random sampling, 36 siswa untuk kelas eksperimen dan 36 siswa untuk kelas kontrol. Instrumen yang digunakan adalah tes. Pengujian hipotesis dengan menggunakan uji-t diketahui bahwa thitung lebih besar dari ttabel (2,399>1,688). Dari hasil analisis diketahui bahwa terdapat perbedaan yang signifikan kemampuan berpikir kritis siswa dengan model Pembelajaran Berbasis Proyek dibandingkan dengan model konvensional.